Cough in exercise and athletes. (December 2017) - Hull, J.H.; Dickinson, J.W.; Jackson, A.R.
Abstract: Cough is the most common respiratory symptom reported by athletes and can significantly impact on health status, ability to train and athletic performance. The presence of cough in an athlete is typically taken to indicate exercise-induced bronchoconstriction (EIB), yet in many athletes with chronic cough there is no objective evidence of airway hyper-responsiveness (AHR) or heightened airway inflammation. Moreover, cough in athletes often fails to respond to a therapeutic asthma strategy, thus further work is urgently needed to progress our understanding of the pathophysiology of exercise-associated cough in this unique population. This article provides an overview of the current state of knowledge of exercise-associated cough in athletes. The article summarises our understanding of pathophysiological basis of cough in this context and provides a pragmatic clinical approach to this problem.